Lessons Learned from Bidirectional Fetal Anomaly Ultrasound Training between Ghanaian and American Maternal–Fetal Medicine Programs - Sarah Boudova; Alim Swarray-Deen; Catalin Buhimschi; Samuel Oppong (The American Journal of Tropical Medicine and Hygiene, 2026)
ABSTRACT. Congenital anomalies cause significant morbidity and mortality globally. Diagnosis and exchange of information about management of fetal anomalies is an essential component of Maternal–Fetal Medicine (MFM) training. Bidirectional partnerships can enhance MFM education and improve patient care. We have modeled a bidirectional fetal anomaly training program between the University of Ghana and the University of Illinois Chicago in which a multidisciplinary team meets virtually once a month and trainees from both universities can present cases for discussion. This approach has been well-received and has expanded the education of fellows at both sites regarding the breadth of pathology and management strategies. Key lessons learned from this collaboration include the importance of mutual and reciprocal learning, long-term partnership, a structured program, multidisciplinary perspectives, and interlacing research with education.